2020
DOI: 10.3390/cryst10030193
|View full text |Cite
|
Sign up to set email alerts
|

Bicontinuous Cubic and Hexagonal Columnar Liquid Crystalline Ion-Conductors at Room Temperature in Ion-Doped Dendritic Amphiphiles

Abstract: A bicontinuous cubic (Cubbi) liquid crystalline (LC) phase consisting of three dimensional (3D) conducting networks is a promising structural platform for ion-conductors. For practical applications using this fascinating LC structure, it is necessary to suppress crystallization at room temperature (RT). Herein, we report the Cubbi structure at RT and the morphology–dependent conduction behavior in ionic samples of a non-crystallizable dendritic amphiphile. In the molecular design, branched alkyl chains were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…■ EXPERIMENTAL SECTION Materials. Figure 1 shows the chemical structure of ILCn (n = 8, 10, 12,14,16). They are denoted as ILC8, 10, 12, 14, and 16.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…■ EXPERIMENTAL SECTION Materials. Figure 1 shows the chemical structure of ILCn (n = 8, 10, 12,14,16). They are denoted as ILC8, 10, 12, 14, and 16.…”
Section: ■ Introductionmentioning
confidence: 99%
“…References , , summarized the design strategies, synthesis, and mesomorphic behavior for various columnar ILCs. However, only a handful of investigations report the molecular mobility of columnar ILCs. , Our previous study addressed the impact of the cation headgroup (cyclic and acyclic) on the dynamics of columnar ILCs and it was observed that both the dynamics and the ionic conductivity slows down for the acyclic ILCs . On the other hand, the influence of alkyl chain length on the dynamics and charge transport in columnar ILCs remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Similar behavior was noted for the next member of the series, namely, THN­(6)­7 (Figure S47a). As mentioned earlier, this behavior can be attributed to the slow response of the discogens to the heat or small enthalpy changes, which may be falling well below the recognition limit of DSC equipment . However, DSC curves of the cooling runs of the other members, namely, THN­(6)­8 , THN­(6)­9 , THN­(6)­10 , THN­(6)­11 , and THN­(6)­12 , comprise two exothermic peaks, implying that these discotics crystallize while cooling from the Col phase (Figure S47b–f).…”
Section: Resultsmentioning
confidence: 81%
“…As mentioned earlier, this behavior can be attributed to the slow response of the discogens to the heat or small enthalpy changes, which may be falling well below the recognition limit of DSC equipment. 29 For compounds belonging to THN( 6)n series, peak temperatures in the DSC traces obtained during the first heating−cooling cycles at 5 °C min −1 are given along with the enthalpies (kJ mol −1 ) of transitions. b The temperature of the phase transitions of tris(hydrazone)s belonging to the THN( 9)n (trialkoxy) series could be determined with the aid of POM only as no events were seen in the DSC traces.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Liquid crystals (LCs) are characterized by the presence of ordered molecules in liquid states. These materials have revolutionized the worldwide information and display 1 industries during the last several decades and they have also found many applications in other fields such as biosensors, 2,3 proton and ion conductions 4–12 and pharmaceutical industries. 13,14…”
Section: Introductionmentioning
confidence: 99%